48% of farmers adopt stress-tolerant rice varieties and improve their yield and income in flood-risk areas in India - CGIAR Research Program on Rice (2021)
The study analyzed the impact of information access and information quality on adoption decisions regarding stress-tolerant rice varieties (STRVs) in flood-risk areas in Assam, Odisha and West Bengal in India. 48 per cent of the farmers having access to information decided to adopt STRVs. From the cultivation of the flood-tolerant variety SS1, the household gained an additional yield of 527-1,023 kg/ha, amounting to an additional income 67-134 $/ha.